Autophagy Related-Protein 16-1 Up-Regulated in Hepatitis B Virus-Related Hepatocellular Carcinoma and Impaired Apoptosis - Peantum, Jiaranai (Gastroenterology Res, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) as primary malignancy of the liver has become the most common type of cancer worldwide. HCC development is mainly caused by viruses, especially the hepatitis B virus (HBV). Autophagy is an important defense mechanism against virus infection; however, HBV promotes autophagy mediated by the HBx protein which stimulates its replication. The autophagy-related protein 16-1 (ATG16L1) binds to the ATG12-ATG5 conjugate and forms a large protein autophagosome complex. Previous studies indicated that the ATG12-ATG5 conjugate was involved in HBV-associated HCC. Therefore, the ATG16L1 protein might consistently relate to this condition. METHODS: Accordingly, the ATG16L1 protein expression was determined in tumor and non-tumor liver cell lines and liver tissue samples using immunoblotting, and also investigated in ATG16L1-knockdown cells to further clarify this function. RESULTS: Our results showed that the ATG16L1 protein was up-regulated in HepG2.2.15 and HepG2 cell lines compared to THLE-2 cells. This protein also increased in tumor liver tissues of HCC patients with HBV infection compared to adjacent non-tumor tissues. Silenced-ATG16L1 also significantly promoted apoptosis in HepG2 cells cultured in starvation conditions. CONCLUSIONS: Findings suggested ATG16L1 as an important molecule involved in apoptosis processes for HCC cells. A more profound understanding is required regarding the mechanisms that link autophagy and apoptosis in HCC development.